If you're not familiar with Pascal's Triangle, see part 1.

# Finding a Formula

How do we leverage the relationship (in the image above) to obtain an equation that obtains the \(z\)th term (\(Fib(z)\), or \(F(z)\)) in the Fibonacci sequence? First, we need to figure out what our equation may look like. We know we're adding up terms of the Fibonacci sequence, so a summation symbol will be used. Additionally, we are adding up terms from Pascal's triangle, where each term individually can be written as \(_nC_r\).So our final equation will look akin to this:

\[\sum_{\varphi=1}^{z_{end}}{_n}C_k\]

But this is not exactly right, since \(n\) and \(k\) are different for each \(\varphi\)th term that's being added up (dependent on the summation index). Therefore, we can more accurately write:

\[Fib(z) = f(z) =\ \sum_{\varphi=1}^{z_{end}}{_{n(\varphi)}}C_{k(\varphi)}\]

Note that the summation index, \(\varphi\) is starting from \(1\). Also, I'm starting Pascal's triangle from a row of 1. So since \(z\) starts at 1, \(z_1 = 1\), \(z_2 = 1\), and \(z_3 = 2\).

I started by reorganizing all the \(_nC_r\) terms from the triangle above into rows. I tried to color the table similarly to the triangle.

One of the first and more obvious patterns is found in the \(z_{end}\) column. Rather than increasing by an increment of \(1\) for every row as the \(z\) colum does, it increases by an increment of \(1\) for every other row.

This is an important pattern because it determines the number of terms being summed.

\[z_{end} = round(\frac{z}{2})\]

Now, we know we can better describe what the summation might look like

\[Fib(z) = f(z) =\sum_{\varphi=1}^{round(\frac{z}{2})}{_{n(\varphi)}}C_{k(\varphi)}\]

So to find the \(4\)th term in the Fibonacci Sequence, or \(z = 4\), we know \(z_{end} = 2\). We're summing \(2\) terms.

\[Fib(4) =\sum_{\varphi=1}^{2}{_{n(\varphi)}}C_{k(\varphi)} =\ _2C_1 +\ _3C_0\]

We only know that \(_2C_1\) and \(_3C_0\) are summed due to the table I wrote above. We don't know why \(n(1) = 2\) or why \(k(2) = 0\) yet.

There are a few other patterns held within the grid. I found it easier to find the pattern by changing which way the terms were summed. As you can see, I rearange the order of the \(_{n(\varphi)}C_{k(\varphi)}\) terms, making the \(\varphi_1, \varphi_2, ...\ \varphi_{th}\) terms somewhat arbitrary (depending on the grid structure rather than concrete values).

Now, you can see a clearer pattern for the \(k(\varphi)\) more easily, now that they're more aligned. It's value is one less than the current summation index value (the \(\varphi\)th term, up to \(z_{end}\)).

\[k(\varphi) = \varphi - 1\]

Now, we just have to determine \(n(\varphi)\). It's slightly harder because it depends on the \(z\)th term and the \(\varphi\)th term. In other words, it depends on the \(z\)th term we're adding to in the Fibonacci sequence and the value of the summation index, \(\varphi\).

\[n(\varphi) = z - \varphi\]

Or, more accurately

\[n(\varphi, z) = z - \varphi\]

Now we have all of the missing parts! Putting it all together, we obtain

\[F(z) = Fib(z) = \sum_{\varphi=1}^{z_{end} = round(\frac{z}{2})}{_{n(\varphi,\ z)\ =\ z - \varphi}}C_{k(\varphi)\ =\ \varphi - 1}\]

Or, more succinctly

\[F(z) = \sum_{\varphi=1}^{round(\frac{z}{2})}{_{z - \varphi}}C_{\varphi - 1}\]

Does this equation give us the \(z\)th term of the Fibonacci sequence by adding up terms of Pascal's triangle? Yes! It conforms to the original goal.

Let \(z = 9\). We obtain

\[F(9) = \sum_{\varphi=1}^{5}{_{9 - \varphi}}C_{\varphi - 1}\]

\[=\ _{9 - 1}C_{1 - 1} + \ _{9 - 2}C_{2 - 1} + \ _{9 - 3}C_{3 - 1} + \ _{9 - 4}C_{4 - 1} + \ _{9 - 5}C_{5 - 1} \]

\[=\ _{8}C_{0} + \ _{7}C_{1} + \ _{6}C_{2} + \ _{5}C_{3} + \ _{4}C_{4} \]

\[=\ 1 + 7 + 15 + 10 + 1\]

\[=\ 34\]

Did make a proof? No. Although I can't conclusively say so, I do believe this works for any \(n\ |\ n \in \mathbb{N}\).